Evaluation of hearing loss by pure tone audiometry in chronic suppurative otitis media patients - Handi, Prakash S.; Patil, Mallikarjun N.; Prasenkumar, K. R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Hearing loss associated with the CSOM affects the patients’ communication with others and results in poor quality of life. Degree and type of hearing loss can be assessed by pure tone audiometry, which helps in predicting the status of tympanic membrane, ossicular chain, and inner ear and also helps in preoperative planning. Methods: Patients with CSOM aged 10 years and above were included in the study. All patients underwent pure tone audiometry. With the help of air and bone conduction threshold, the degree and type of hearing loss in each ear was determined. The data collected was evaluated and results are reported as rates and proportions (%). Results: Most of the ears (83%) had mild to moderate hearing loss. Average ABG observed was 31 dB. Maximum ABG observed was 55dB on right side and 50 dB on the left side. There was mixed hearing loss in 10.9% cases. Conclusions: This study reinforces the idea of using preoperative pure tone audiometry, which not only helps in planning surgery but also helps in documenting the preoperative status of patients’ sensorineural hearing loss, if present.